2011
DOI: 10.1007/s00428-011-1103-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of histone deacetylases 1, 2, 3, and 7: HDAC2 is an independent predictor of survival in HCC

Abstract: Histone deacetylases (HDAC) are responsible for the transcriptional control of genes through chromatin remodeling and control tumor suppressor genes. In several tumors, their expression has been linked to clinicopathological factors and patient survival. This study investigates HDACs 1, 2, 3, and 7 expressions in hepatocellular carcinoma (HCC) and their correlation with clinical data and patient survival. Tissue microarrays of 170 surgically resected primary HCCs and adjacent uninvolved tissue were evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(70 citation statements)
references
References 33 publications
6
64
0
Order By: Relevance
“…Among class 1 HDAC family members, the expression of HDAC1 was reported to be altered in liver cancers and hdac1 also regulate zebrafish liver formation (Farooq et al, 2008;Wu et al, 2010;Yang et al, 2010;Quint et al, 2011;Lachenmayer et al, 2012). This suggests a critical role of HDAC 1 in liver formation and liver carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among class 1 HDAC family members, the expression of HDAC1 was reported to be altered in liver cancers and hdac1 also regulate zebrafish liver formation (Farooq et al, 2008;Wu et al, 2010;Yang et al, 2010;Quint et al, 2011;Lachenmayer et al, 2012). This suggests a critical role of HDAC 1 in liver formation and liver carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Very little is known about the possible contribution of HDAC in liver cancer progression or metastases. However, HDAC expression has been reported to be altered in liver cancer tissues (Quint et al, 2011;Wu et al, 2010). The available data on the role of HDACs in cancer indicated that there is more than one mechanism by which HDACs function in cancer development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This acetylation equilibrium is profoundly disturbed in HCC by an imbalance between functioning of HATs and HDACs driven mainly by an abnormally high HDAC activity. Specifically, the results of several studies have demonstrated an overexpression of histone deacetylases HDAC1, HDAC2, HDAC3, HDAC5, and HDAC7 in human HCC (148)(149)(150). Additionally, it has been reported that genetic polymorphisms in the HDAC1 and HDAC3 or in the promoter of the HDAC10 genes are associated with the development or reoccurrence of HCC (151,152).…”
Section: Inhibition Of Hdacs By Bioactive Food Constituents and Prevementioning
confidence: 99%
“…Hepatic carcinoma, one of the most common malignant tumor in China, was found later (Quint et al, 2011;Chen et al, 2014;Page et al, 2014;Scaggiante et al, 2014). The incidence of HCC is increasing, particularly in China, due to the high prevalence of hepatitis virus infection, which confers a high risk of HCC (Ji et al, 2014;Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%